An analytic framework to advance understanding of power sector reforms in Sub-Saharan Africa - Hampton, Brent (Department of Electrical Engineering, 2024)
This thesis seeks to advance knowledge of electricity sector reform by providing a framework of critical elements of sector reform for analyzing the context of proposed reform and to provide a basis for preparing sustainable reform policy. Modern market-based electricity sector reforms were first implemented in Chile in 1979 followed by the UK in 1990. This model of reform continued to be used globally as the basis for reform over a period of more than 30 years. While the approach has proved moderately successful in some developed countries, the outcomes in developing countries, and particularly in Sub-Saharan Africa, have been generally unsatisfactory. The expected improvements in utility efficiency, access and private sector financing have mostly not materialized. The direction regarding reform policy going forward is currently unclear and a return to the drawing board appears to be imminent. The research involves a deep review of the origins and spread of market-based reforms and outcomes, with a focus on developing countries, and Sub-Saharan African countries in particular. A set of critical elements impacting sector reform outcomes was identified from analysis of the literature and field research and developed into a proposed framework of analysis with three tiers and a set of cross cutting elements. Verification of the plausibility of the analytic framework was carried out using a two-pronged approach. First, a set of three in depth Sub-Saharan Africa country case studies was undertaken, covering each element in the framework. Secondly a set of interviews was conducted with a spectrum of senior stakeholders from the sector to establish views on the importance and scope of each element of the framework. Both methods confirmed that the proposed framework was a valid, adequate and robust tool for analyzing the sector and likely reform outcomes, and that the proposed working hypothesis did not adequately cover the requirements for effective reform policy. The research has implications for international development funding and the attainment of Sustainable Development Goal 7 (access to clean energy) and may be extended to other sectors.